IMPLEMENTASI PP NO 46 TAHUN 2013 TERHADAP KEPATUHAN WAJIB PAJAK UMKM DI KOTA JAMBI - Tiswiyanti, Wiwik; Wendry, Widyasari (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2019)
The research aims to analyze the effect of the implementation of PP No. 46 of 2013 towards taxpayer compliance in MSMEs in the city of Jambi. The population in this research is Clothing UMKM which consists of UMKM Cloth Songket and Embroidered UMKM in Jambi City as tax objects Government Regulation No. 46 of 2013. With a sample of 30 UMKM. Data was collected using a questionnaire. Data analysis techniques using Simple Regression Analysis. The research results show that the Implementation of Government Regulation No. 46 has a positive effect on the compliance of taxpayers who can be appointed the value of t count is greater than the value of t table that is 3.73 1> 2.045 and the significance of 0.001 is less than 0.005 which indicates that the Implementation of PP No. 46 of 2013 has an effect on taxpayer compliance.